2020
DOI: 10.1155/2020/5839837
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Structural Changes Assessed with Swept-Source Optical Coherence Tomography after Cataract Surgery in Eyes with Diabetic Retinopathy

Abstract: Objective. To determine the influence of phacoemulsification on choroidal vasculature in patients with diabetic retinopathy (DR) undergoing cataract surgery using swept-source optical coherence tomography (SS-OCT). Methods. The study was conducted in 23 eyes of 23 cataract patients with mild/moderate nonproliferative diabetic retinopathy (NPDR) without diabetic macular edema (DME) and 23 age-matched controls. Choroidal thickness (CT) and choroidal vascularity index (CVI) were measured at baseline and 1 week, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
2
7
0
1
Order By: Relevance
“…In addition to providing nutrients to the retina, the choroid seems to play an important role in the development of DR. Hyadat et al reported in 1985 that in diabetic eyeschoriocapillaris, there is basement membrane thickening, capillary dropout and narrowing of the lumen and that choroidal arteries show arteriosclerotic changes [ 3 ]. These observations suggest that choroidal vasculopathy, further identified as diabetic choroidopathy (DC), might play an important role in the evolution of DR [ 3 , 4 ]. Fryczkowski et al identified, by scanning electron microscopy (SEM) studies, increased tortuosity, dilation and narrowing, hypercellularity, vascular loops and microaneurysms, “drop-out” of choriocapillaris and sinus-like structure formation between choroidal lobules [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing nutrients to the retina, the choroid seems to play an important role in the development of DR. Hyadat et al reported in 1985 that in diabetic eyeschoriocapillaris, there is basement membrane thickening, capillary dropout and narrowing of the lumen and that choroidal arteries show arteriosclerotic changes [ 3 ]. These observations suggest that choroidal vasculopathy, further identified as diabetic choroidopathy (DC), might play an important role in the evolution of DR [ 3 , 4 ]. Fryczkowski et al identified, by scanning electron microscopy (SEM) studies, increased tortuosity, dilation and narrowing, hypercellularity, vascular loops and microaneurysms, “drop-out” of choriocapillaris and sinus-like structure formation between choroidal lobules [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al evaluated CVI in patients with diabetic cataracts and reported a significant increase after surgery [ 1 ]. In contrast to an earlier study suggesting that changes in intraocular pressure after cataract surgery might lead to changes in choroidal thickness [ 20 ], Yao et al found no significant postoperative difference in intraocular pressure, despite a decrease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al evaluated CVI in patients with diabetic cataracts and reported a significant increase after surgery [ 1 ]. In contrast to an earlier study suggesting that changes in intraocular pressure after cataract surgery might lead to changes in choroidal thickness [ 20 ], Yao et al found no significant postoperative difference in intraocular pressure, despite a decrease [ 1 ]. Similarly, in the current study, there was a decrease in intraocular pressure at the first and third postoperative month evaluations, but this was not statistically significant with respect to the measurement made before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher levels of proinflammatory cytokines and vascular endothelial growth factor in the choroid of patients with diabetic retinopathy may be one of the underlying mechanisms of the upregulating expression postoperatively, which is demonstrated to induce a higher increase in CVI in patients with mild to moderate nonproliferative diabetic retinopathy than in nondiabetic patients after cataract surgery. 30 …”
Section: Discussionmentioning
confidence: 99%